The Dilemma of Financial Autonomy in the Management of Public Finances at the Level of Local Governments - Mohamed Mouloud Belaid; Yamina Soudani; Alina Iuliana Tabirca (Ovidius University Annals: Economic Sciences Series, 2023)
This research analyzes a group of municipalities in Algeria from the perspective of financial autonomy in the management of public finances at the level of local administrations. Local public finances in Algeria have not been as severely impacted as the State’s during the global health crisis 2020, but this is more concerning than reassuring. Ironically, the reason for this is the same as what made the municipality the “driving force” of local development, a sub-national entity heavily reliant on state aid: financial constraints. As a result, this study aims to reflect on the reality of the local government's financial management through a survey conducted in Annaba’s wilaya and, more specifically, in the municipality of Annaba, El-Bouni, Berrahal, El-Hadjar, and Sidi Amar. As a result, it was necessary to inquire about the obstacles that needed to be overcome to lay the groundwork for more effective local financial management and the local community’s aspirations.